How to Assess Digital Literacy Skills of Elementary School Students? - Suwanto; Lestari, Wiwik (Indonesian Scientific Publication, 2024)
Students need digital literacy skills to face the 21st century, so teachers must monitor the development of their digital literacy skills. Therefore, instruments are needed to monitor digital literacy skills, but the instruments currently available have not taken into account the psychological, cognitive, and psychomotor development of elementary school children, even though they have limitations in accessing digital devices and limited vocabulary. These problems prompted the need for instrument development using the modified Tiagarajan 4-D development model, Difine, Design, and Development. Instrument development criteria must meet the validity and practicality of the instrument. The instrument was prepared using the Google Form platform, consisting of 13 statements in the form of a Likert questionnaire and 22 statements in the form of an essay test. Qualitative data were analyzed by data collection, data reduction, data presentation, and data verification, while descriptive statistics and item analysis analyzed quantitative data. The instrument design was validated by five validators with a validation level of 3.4, which was declared valid, although the instrument had to be revised. Then the instrument trials were carried out and the quality of the instruments was obtained with a validity level of 19 questions declared valid, 3 quite valid, and 3 very valid, while the Reliability Level was 0.885 for the questionnaire and 0.871 for the test instrument. At the same time, the level of practicality of the instrument was obtained from the teacher's response to the instrument at 76.1 or practical. Even though it meets practical, valid, and effective criteria, apart from having to present it through digital devices, attention needs to be paid to the ability to use symbols and tools and at a minimum must fulfill information skills, digital tools usage, and digital transformation.